A punção subaracnoidea sobre tatuagem determina alterções histológicas sobre o tecido nervoso e as meninges? - Ferraz, Isabela Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Body tattooing is part of many peoples culture in the world. Since 1990, it has been used as a body art. The tattoo pigments may contain organic and inorganic compounds, metals and solvents. The implications of performing regional anesthesia on tattooed skin are poorly known. There are no documented evidence or scientific proof that tattoo pigments can cause arachnoiditis or other neurological complications. Objectives: to assess whether spinal puncture performed on the tattooed skin of rabbits determine histological changes in the spinal nerve tissue and meninges. To analyze the presence of fragments of ink inside of needles. Methods: 36 rabbits were randomized in 3 groups (G). G1 puncture on tattoos, G2 spinal puncture on tattoos and injection of saline, G3 spinal puncture and injection of saline. The spinal puncture was ultrasound guided and performed under anesthesia in the space between the first and second sacral vertebra (a 22G 21/2 Quincke needle was used). The animals in the groups 2 and 3 received a 5 μl/cm spine volume solution (0,2 cc). The animals in the group 1 underwent only sacral puncture and, after that, was injected through the needle 1 cc of saline. The goal was to obtain histological material for conducting smear and possible identification of the tissue. The animals were evaluated clinically for 6 months. After this time they were sacrificed and have the lumbar and sacral portions of the spinal cord removed under anesthesia for histological examination by light microscopy. Results: pigments of ink was noted in all G1 smears material of needles. Perivascular lymphocytic infiltrate was noted in focal areas of the meninges in 33% of rabbits in group 2. Nervous tissue, meninges and blood vessels were normal in G3. Conclusion: subarachnoid puncture on the tattooed skin caused histological changes in the meninges, but not in the spinal nervous tissue. Fragments of tattoo ink were found inside of needles, despite the ...

O hábito de tatuar o corpo faz parte da cultura de muitos povos no mundo. A partir de 1990, passou a ser utilizado como forma de arte no corpo. Os pigmentos da tatuagem podem conter componentes orgânicos e inorgânicos, metais e solventes. Pouco se conhece sobre as implicações da realização de anestesia regional sobre pele tatuada. Não existem evidências documentadas ou provas científicas de que os pigmentos da tatuagem possam causar aracnoidite ou outras complicações neurológicas. Objetivos: avaliar se a punção subaracnoidea realizada sobre a pele tatuada de coelhos determinaria alterações histológicas no tecido nervoso medular e nas meninges. Analisar presença de fragmentos de tinta no interior das agulhas de punção. Metodologia: foram utilizados 36 coelhos randomizados em 3 grupos (G): G1 punção sobre tatuagem, G2 punção subaracnoidea sobre tatuagem e injeção de solução fisiológica e G3 punção subaracnoidea e injeção de solução fisiológica. A punção (agulha de Quincke 22G 21/2) foi realizada sob anestesia no espaço entre a primeira e a segunda vértebra sacral guiada por ultrassom. Os animais de G2 e G3 receberam soluções em volume de 5 μL/cm de coluna vertebral (0,2 mL) e nos de G1 foi realizado somente punção sacral e, após esta, foi injetado, através da agulha, 1 mL de solução fisiológica sobre lâmina histológica para realização de esfregaço para possível identificação do tecido. Os animais foram avaliados clinicamente por 6 meses, após os quais foram decaptados sob anestesia e retiradas as porções lombar e sacral da medula espinhal para exame histológico por microscopia óptica. Resultados: presença de pigmentos de tinta em todos os esfregaços dos materiais das agulhas de punção do G1. Infiltrado linfoplasmocitário perivascular em áreas focais das meninges em 33% dos coelhos de G2. Tecido nervoso, meninges e vasos sanguíneos normais em G3. Conclusão: a punção ...
Does the neuroaxial blockade in the presence of tattoos cause histological changes on the spinal nerve tissue and meninges
Keywords: Histologia; Coelho como animal de laboratorio; Tatuagem; Meninges; Sistema nervoso central - Doenças; Tattooing